Beyond the bubble test : how performance assessments support 21st century learning - Darling-Hammond, Linda, 1951-; Adamson, Frank (San Francisco, CA : Jossey-Bass & Pfeiffer Imprints, Wiley, 2014)
Educators are unhappy with the current assessments and their focus on low-level skills like recalling and restating facts rather than higher-order skills such as problem-solving and analyzing and synthesizing information. This book examines performance assessment as an alternative to the current high stakes standardized testing system in theUnites States. A must-have resource for those interested in the current research of performance assessment in the 21st century, this book will help educators accurately assess the benefits and possibilities for adopting performance assessments nation ...
Introduction : the rationale and context for performance assessment -- Looking back : performance assessment in an era of standards-based educational accountability -- Where we are now : lessons learned and emerging directions -- Reaching out : international benchmarks for performance assessment -- Performance assessment : the state of the art -- Adapting performance assessments for English language learners -- Supporting teacher learning through performance assessment -- A new conceptual framework for cost analysis -- Investing in assessments of deeper learning : the costs and benefits of tests that help students learn -- Building systems of assessment for deeper learning -- Concluding thoughts : creating next-generation assessments that last.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Educational tests and measurements -- United States; Curriculum-based assessment; Exceptional children -- Rating of; Electronic books; Electronic books